Are the spectral Doppler indices of ovarian arteries indicative of antral follicular development and predictive of ovulatory responses and embryo yields in superovulated ewes? - Franco Oliveira, Maria Emilia [UNESP]; Fonseca, Jeferson Ferreira; Russiano Vicente, Wilter Ricardo [UNESP]; Rodrigues, Naiara Nantes [UNESP]; Vergani, Gabriel Brun [UNESP]; Goncalves Souza-Fabjan, Joanna Maria; Jamieson, Mark; Cristescu, Ada; Murawski, Maciej; Bartlewski, Pawel Mieczyslaw (Inst Animal Reproduction Food Research, 2019)
Nineteen ewes received 200 mg of pFSH administered in eight decreasing doses from Days 1 to 4, starting three days before CIDR (R) device removal. Ten ewes received an injection of 350 mu g of estradiol benzoate at CIDR (R) device insertion (Group E) and nine animals served as controls (Group C). B-mode and spectral Doppler ultra-sonographic examinations were performed daily throughout superovulatory treatment to enumerate ovarian antral follicles and to determine ovarian blood flow indices, respectively. There were no differences (P > 0.05) in superovulatory responses between left and right ovaries/uterine horns or the two groups of animals. End-diastolic velocity (EDV) and mean velocity (Vm) values were greater (P < 0.05) on Days 1 and 2, and peak systolic velocity (SVp) was greater (P < 0.05) on Day 3 in Group C than in Group E. In Group E 15 correlations was recorded among indices (SVp, Vm, EDV, flow velocity integral-FVI, and pulsatility index-PI) and follicles numbers in different size classes on Days 1, 2 and 4, and seven correlations among indices (SVp, EDV, Vm, and vascular resistance index-RI) and superovulatory/embryo results (numbers of regressing corpora lutea, numbers/percentages of degenerated embryos and viability rates) on Days 1, 2 and 3. In Group C, there were three correlations among EDV and RI and medium-sized/large follicle numbers on Days 1 and 3, and five correlations among indices (EDV, RI and PI) and superovulatory/embryo results (numbers of luteinized unovulated follicles, degenerated embryos and unfertilized eggs) on Days 2 or 4. There was a lack of consistency in the velocimetric correlates of antral follicle numbers and superovulatory responses between the left and right side. Therefore, the usefulness of ovarian arterial indices to predict ovine superovulatory outcomes remains equivocal and requires further confirmatory studies.
Keywords: Sheep; Superovulation; Estradiol benzoate; Doppler ultrasonography; Ovarian artery